Kajian Motivasi Tematik Perspektif Al Quran - Yadi, Robai; Mahmud, Hamidullah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study aims to describe how the study of thematic motivation of the Qur'an, The data collection technique is using library research or library study research with data collection techniques carried out by examining literature, documents, and other sources of information related to the topic of researchers. The results of this study Motivation in the perspective of the Qur'an has a very strong foundation, where all forms of encouragement and human intentions to take an action must be based on the pleasure of Allah. In Islamic teachings, true motivation is not only to pursue worldly success, but also to achieve happiness and safety in the hereafter. The Qur'an emphasizes the importance of sincerity in every action, as reflected in verses that motivate humans to do good and be pious. Keywords: Al Quran, Motivation, Thematic Interpretation